Floating modular drug delivery systems with buoyancy independent of release mechanisms to sustain amoxicillin and clarithromycin intra-gastric concentrations. (1st February 2016) - Rossi, Alessandra; Conti, Chiara; Colombo, Gaia; Castrati, Luca; Scarpignato, Carmelo; Barata, Pedro; Sandri, Giuseppina; Caramella, Carla; Bettini, Ruggero; Buttini, Francesca; Colombo, Paolo
Abstract: Release modules of amoxicillin and clarithromycin combined in a single dosage form designed to float in the gastric content and to sustain the intra-gastric concentrations of these two antibiotics used for the eradication of Helicobacter pylori have been studied. The modules having a disc shape with curved bases were formulated as hydrophilic matrices. Two modules of clarithromycin were assembled by sticking the concave base of one module to the concave base of the other, creating an internal void chamber. The final dosage form was a floating assembly of three modules of clarithromycin and two of amoxicillin in which the drug release mechanism did not interfere with the floatation mechanism. The assembled system showed immediate in vitro floatation at pH 1.2, lasting 5 h. The in vitro antibiotics release profiles from individual modules and assembled systems exhibited linear release rate during buoyancy for at least 8 h. The predicted antibiotic concentrations in the stomach maintained for long time levels significantly higher than the respective minimum inhibitory concentrations (MIC). In addition, an in vivo absorption study performed on beagle dogs confirmed the slow release of clarithromycin and amoxicillin from the assembled system during the assembly's permanence in the stomach for at least 4 h.